Detailed Research on a Comparative Evaluation of Diclofenac Sodium Tablets Manufactured by Using DC Grade Excipients and Wet Granulation Methods - Kara, Divya Dhatri; Govindarajulu, Hemanth Katta; Shivaprasad, Hemamanjushree; Tippavajhala, Vamshi Krishna; Joshi, Mahendra; Kulyadi, Girish Pai (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The foremost aim of the present study was to formulate a Diclofenac Sodium tablet of 50mg using the direct compression method with directly compressible (DC) grade excipient and the wet granulation method. Materials and Methods: Comparative study of evaluation parameters like micromeritic properties of directly compressible powder blends and granules obtained by wet granulation was carried out to analyze the suitable method for tabletting. Evaluation parameters such as tablet description, hardness, friability, drug content, disintegration time, and dissolution study were analyzed and compared for tablets manufactured by direct compression using DC grade excipients and wet granulation methods. Results: The results of all evaluation parameters were well within the limit as per Indian Pharmacopeia (IP). Edges and Surface morphology of tablets were studied using Scanning Electron Microscopy (SEM). In-process hold time for tablets was studied by performing hold time stability study. The present work was also focused on the comparison of tablets physicochemical properties manufactured from direct compression using DC grade excipient and wet granulation methods. Conclusion: The results of disintegration and dissolution studies revealed that the tablets manufactured using direct compression using DC grade excipients were completely disintegrated in a short time and steadily dissolved at a faster rate respectively compared to the tablet manufactured from wet granulation method. Hold time stability study showed that the directly compressible tablets were more stable than the tablet formulated using the wet granulation method.
Keywords: Direct compression; Directly compressible (DC) grade excipients; Wet granulation; Scanning Electron Microscopy (SEM); Surface morphology; Hold time stability study